World economic survey 1979-1980 : current trends in the world economy - United Nations (New York : United Nations publication, 1979)
This report contains a world economic survey, with emphasis on the current trends around the world.
asm 23/01/2019
Ref.
Keywords: Economic history; International economics; Futuring; Cooperation; Economic conditions; Trade, International